Les moyens sémantico-rhétoriques de valorisation dans les structures axiologiques de l’éditorial sociopolitique - Topa-Bryniarska, Dominika (Neophilologica, 2013)
The following article discusses problems concerning the persuasive function of semantic and rhetorical means used to express evaluations and judgements in a special type of media discourse called editorial. By using different semantic and rhetorical means of valorization, journalists construct the axiological domain of discursive representation in order to influence and manipulate the readers’ feelings and opinions. Therefore, the author of the study focuses her attention on two types of linguistic means of valorization such as axiological expressions (J-C. Anscombr e, O. Ducrot, 1988) and persuasive metaoperators (according to A. Awdiejew’s terminology, 2004) whose purpose is to reinforce the information content. Both elements are connected with language manipulation.